Development of discrete event system (DES)-based controller - Fatai, Sado; Sidek, Shahrul Na'im (IIUM Press, International Islamic University Malaysia, 2017)
The importance of robotic devices for upper-limb rehabilitation therapy has been underscored by clinical evaluation of some existing robotic platforms. The devices have been used largely with the aid of expert human therapists who are required to specify appropriate therapy placement and adjust the therapy in consonant with the patient physical recovery, active participation, or motor control performance. A survey on the control strategies, however, for most of the rehabilitation robots reveals that, although the robotic systems allow several task specifications aimed at inducing motor plasticity, their control strategies can be considered static or “low-level” in that they do not adapt control parameters to the physical recovery condition of the patients. Hence, with increase in the population of stroke patients compared with the few available therapists, it is crucial to have an adaptive system that can assume closely the role of an expert therapist by sensing the patients’ muscle tone, physical recovery condition, or sensorimotor control performance to specify appropriate therapy and to provide assessment.